2017
DOI: 10.5301/jva.5000750
|View full text |Cite
|
Sign up to set email alerts
|

Factors Causing Loss of Normal Doppler Waveform of the Left Internal Jugular Vein: Evaluation on Chest Computed Tomography

Abstract: It is necessary to suspect steno-occlusive lesion of the LBCV from various causes and to use caution when performing central venous catheterization in cases with loss of a normal Doppler waveform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(43 reference statements)
0
2
1
Order By: Relevance
“…There were no cases of central vein stenosis in this study in the absence of the risk factors we identified. This is in contrast to some studies that reported prevalence of central vein abnormalities ranging from 6% to 63% in patients without obvious risk factors for stenosis (7,(10)(11)(12)30). Although factors such as extrinsic compression or hemodynamic stress could contribute to central vein stenosis, our data suggest that their contribution to prevalence of central vein stenosis in the general population of patients with advanced CKD may be less important than previously reported.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There were no cases of central vein stenosis in this study in the absence of the risk factors we identified. This is in contrast to some studies that reported prevalence of central vein abnormalities ranging from 6% to 63% in patients without obvious risk factors for stenosis (7,(10)(11)(12)30). Although factors such as extrinsic compression or hemodynamic stress could contribute to central vein stenosis, our data suggest that their contribution to prevalence of central vein stenosis in the general population of patients with advanced CKD may be less important than previously reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Until additional data that clarify indications for implantable cardioverter defibrillators in the dialysis population are available, use of leadless pacemakers and defibrillators, or devices with epicardial rather than transvenous leads would be appropriate in those patients suitable for these kinds of devices (23,28). Central vein stenosis could occur in the absence of central vein instrumentation due to extrinsic compression by narrow thoracic inlet, dilated arteries, or benign or malignant growths in adjacent structures (7,20,21). In addition, reports of central vein abnormalities or stenosis in patients on hemodialysis without history of catheters have given rise to the hypothesis that high blood flow rates through fistulas or grafts could directly cause endothelial injury, which in turn leads to neointimal proliferation and stenosis (10,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation